Information and communication technology (ICT) in education - Makhkamova Dilshodakhon Khabibjon qizi (Zien Journals, 2022)
This article discusses the effectiveness of the use of information and communication technologies in education. The article discusses the use of computer game technology in the educational process.
Keywords: Education; ICT; computer; quiz